Pedagogical Implications of the Buddhist Philosophy: A Great Antiquity for Today’s Education - Raj Mishra, Nirmal (Education and Development, 2026)
This paper explores the pedagogical implications of the Buddhist philosophy for classroom teaching. Specifically, this paper discusses the aims of education, teaching methods, curriculum/subjects, role of teachers and students from the perspective of the Buddhist philosophy. This qualitative study employed the library study method to explore the multiple realities of the pedagogical dimensions of the Buddhist philosophy. During the library study, I collected different books, research articles and papers. Based on these documents, I explored that the main aim of education in the Buddhist philosophy is to achieve Nirvana from suffering and ignorance. The role of educational institutions is to promote the moral and character development of an individual. For this, the realization of the four noble truths is necessary and needs to be incorporated in the school's curriculum. The eight-fold paths (Astha Marga) are the methods to achieve Nirvana from sufferings in life. Thus, this philosophy suggests that a teacher must have ethical character in teaching the four noble truths. Likewise, both teachers and students need to spend their lives in simplicity, celibacy, morality, constant study and strength of character. Along with this, teachers should be close with their students and behave affectionately with them